Respuesta :
Answer:
B, C, E, F
Step-by-step explanation:
Multiplying the equation by a constant does not change the solution set. When some terms are changed and others are not, the equation is a different equation.
A) different equation
B) multiplied by -1
C) multiplied by 5
D) different equation
E) multiplied by 2
F) multiplied by 1/2
G) different equation
ANSWER
[tex]B,C,E \: and \: F[/tex]
EXPLANATION
The given equation is
[tex]3x + 2y = - 12[/tex]
The solution to this equation can be found by making y the subject.
[tex]
\Rightarrow \: 2y = - 3x - 12[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This equation has infinitely many solution. Any real value we choose for x, there is a corresponding y-value.
To find which of the given options also has the same solution, we make y the subject.
A
[tex]3x - 2y = 12[/tex]
[tex]
\Rightarrow \: - 2y = - 3x + 12[/tex]
[tex]
\Rightarrow \: y = \frac{3}{2} x - 6[/tex]
This is not the same as the given equation.
B
[tex] - 3x - 2y = 12[/tex]
[tex]
\Rightarrow \: - 2y = 3x + 12[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This solution is the same as the one given.
C.
[tex]15x + 10y = - 60[/tex]
[tex]
\Rightarrow \: 10y = - 15x - 60[/tex]
[tex]
\Rightarrow \: y = - \frac{15}{10} x - \frac{60}{10} [/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This is the same as the above solution.
D.
[tex]6x + 2y = - 12[/tex]
[tex]
\Rightarrow \: 2y = - 6x - 12[/tex]
[tex]
\Rightarrow \: y = - 3 x - 6[/tex]
This is not the same as the one given.
E.
[tex]6x + 4y = - 24[/tex]
[tex]
\Rightarrow \: 4y = - 6x - 24[/tex]
[tex]
\Rightarrow \: y = - \frac{6}{4} x - \frac{24}{4} [/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This is the same as the one given.
F.
[tex]1.5x + y = - 6[/tex]
[tex]
\Rightarrow \: y = - 1.5x - 6[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
Thus is the same as the one given.
G.
[tex]x + \frac{2}{3} y = - 12[/tex]
[tex]
\Rightarrow \: \frac{2}{3} y = - x - 12[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 12 \times \frac{3}{2} [/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 18[/tex]
This is not the same as the one given.
[tex]B,C,E \: and \: F[/tex]
EXPLANATION
The given equation is
[tex]3x + 2y = - 12[/tex]
The solution to this equation can be found by making y the subject.
[tex]
\Rightarrow \: 2y = - 3x - 12[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This equation has infinitely many solution. Any real value we choose for x, there is a corresponding y-value.
To find which of the given options also has the same solution, we make y the subject.
A
[tex]3x - 2y = 12[/tex]
[tex]
\Rightarrow \: - 2y = - 3x + 12[/tex]
[tex]
\Rightarrow \: y = \frac{3}{2} x - 6[/tex]
This is not the same as the given equation.
B
[tex] - 3x - 2y = 12[/tex]
[tex]
\Rightarrow \: - 2y = 3x + 12[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This solution is the same as the one given.
C.
[tex]15x + 10y = - 60[/tex]
[tex]
\Rightarrow \: 10y = - 15x - 60[/tex]
[tex]
\Rightarrow \: y = - \frac{15}{10} x - \frac{60}{10} [/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This is the same as the above solution.
D.
[tex]6x + 2y = - 12[/tex]
[tex]
\Rightarrow \: 2y = - 6x - 12[/tex]
[tex]
\Rightarrow \: y = - 3 x - 6[/tex]
This is not the same as the one given.
E.
[tex]6x + 4y = - 24[/tex]
[tex]
\Rightarrow \: 4y = - 6x - 24[/tex]
[tex]
\Rightarrow \: y = - \frac{6}{4} x - \frac{24}{4} [/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
This is the same as the one given.
F.
[tex]1.5x + y = - 6[/tex]
[tex]
\Rightarrow \: y = - 1.5x - 6[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 6[/tex]
Thus is the same as the one given.
G.
[tex]x + \frac{2}{3} y = - 12[/tex]
[tex]
\Rightarrow \: \frac{2}{3} y = - x - 12[/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 12 \times \frac{3}{2} [/tex]
[tex]
\Rightarrow \: y = - \frac{3}{2} x - 18[/tex]
This is not the same as the one given.